ANALISIS HUBUNGAN INDEKS HARGA SAHAM DOMESTIK, INDEKS HARGA SAHAM INTERNASIONAL, DAN KURS: PENDEKATAN VECTOR AUTOREGRESSION (VAR) - A. J. Ibnu Wibowo (Bina Ekonomi, 2011)
This research aims to analyze the relation between domestic share price index variable (composite share price index), international share indexes, and Rp/US exchange rate simultaneously.  This research uses weekly data along August 2007-April 2008 period. The data is then analyzed with vector autoregression method (VAR). The  result of analysis with impulse response  function  shows  that IHSG variable tends  to give positive  response  towards  shock of exchange  rate variable, Dow Jones Index, Hangseng Index, Singapore  Index, or Nikkei  Index. Meanwhile,  the analysis of variance decomposition shows  that along 10 observations periods,  /HSG variable  tends to give the biggest average contribution (49%-100%) towards  the movement of /HSG variable, while Singapore's index variable gives the smallest average  contribution (0%-2,9%).